1979
DOI: 10.1007/bf00558440
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term high-dose treatment with methenamine hippurate on urinary infection in geriatric patients with an indwelling catheter

Abstract: An evaluation has been made of the clinical and laboratory effects of short-term (34 days), high-dose (2g x 3 daily) treatment with methenamine hippurate (MH) of 14 geriatric patients with an indwelling catheter and clinical features of urinary tract infection. During MH treatment the number of catheter changes was halved, each catheter remaining in situ for an average of 12.0 days as compared to 6.2 days in the pre-treatment control period and 5.2 days in the post-treatment control period; the difference is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The foul smell of urine around patients with urine incontinence is thought to be attributable mainly to the production of ammonia from urea by bacterial ureases [114]. Foul-smelling and/or cloudy urine is often interpreted as warranting antimicrobial treatment in catheterized patients with bacteriuria [115].…”
Section: Evidence Summarymentioning
confidence: 99%
“…The foul smell of urine around patients with urine incontinence is thought to be attributable mainly to the production of ammonia from urea by bacterial ureases [114]. Foul-smelling and/or cloudy urine is often interpreted as warranting antimicrobial treatment in catheterized patients with bacteriuria [115].…”
Section: Evidence Summarymentioning
confidence: 99%
“…Using a before-and-after intervention design, oral methenamine hippurate therapy (2-6 g/d) was found to reduce the incidence of bacteriuria, 77,78 symptomatic UTI, 79 and pyuria. 80 One large, nonrandomized, comparative trial 81 found that patients receiving methenamine hippurate had significantly fewer courses of antibiotic drug therapy for symptomatic UTI and less frequent mechanical catheter complications. Other studies, 82 however, have not found any benefit of methenamine therapy in suppressing catheter-associated bacteriuria.…”
Section: Methenamine Hippuratementioning
confidence: 99%
“…First, antibiotics were re placed by methenamine hippurate, which has no ecological side effects. The function time of silicone-coated latex catheters was dou bled during treatment with methenamine hippurate but bacteriuria and pyuria per sisted [15,16], Then an attempt was made to make latex catheters bactericidal by coating with copper metal; the attempt has, however, not been a clinical success hitherto [17],…”
Section: Discussionmentioning
confidence: 99%
“…The use of indwelling catheters in the management of aged patients with urinary' incontinence is associated with a non-controllable nosocomial situation [7,15,16]. It is suggested that catheters be replaced by diapers whenever possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation